Intermediate structural state in Bi1−xPrxFeO3 ceramics at the rhombohedral–orthorhombic phase boundary - Karpinsky D.V. (2019)
Crystal structure of the Bi1−xPrxFeO3 ceramics of the compositions corresponding to the threshold concentrations separating the polar rhombohedral (R3c) and anti-polar orthorhombic (Pbam) phases has been investigated with X-ray diffraction, transmission electron microscopy and differential scanning calorimetry measurements performed in a broad temperature range. The structural study specifies the peculiarities of the temperature-driven transition into the non-polar orthorhombic (Pnma) phase depending on the structural state of the compounds at room temperature. The crystal structure analysis reveals the revival of the anti-polar orthorhombic phase upon the temperature-induced transition, thus assuming that it can be considered as the bridge phase between the polar rhombohedral and the non-polar orthorhombic phases.